Research of control system of polymeric extrusion process under conditions of disturbances - Жученко, Олексій Анатолійович; Анікеєв, Олександр Овсійович (Eastern-European Journal of Enterprise Technologies, 2014)
The analysis concerning the importance of maintaining a given temperature mode of an extruder while manufacturing polymer materials was carried out. An adaptive system of controlling the temperature mode of the extruder in a normal operating mode under conditions of disturbances of different nature was studied. The adaptive control system is based on the autoregressive-moving average model, uses the recursive least-squares method and its modifications for estimating the model parameters. The studies of the adaptive control system were carried out by introducing disturbances into the system operation. Changes of the power consumption of heat, for example, due to the dissipation of mechanical energy, were considered as the disturbances. The proposed control system of the polymer extrusion process has shown high efficiency under conditions of disturbances of different nature, confirmed by the given results of the conducted studies.